1966
DOI: 10.1515/zna-1966-0745
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Age of Swiss Lake Dwellings as an Example of Dendrochronologically-Calibrated Radiocarbon Dating

Abstract: Comparison of the radiocarbon content of a series of samples of dendrochronologically dated bristlecone pine wood with that from trees for which a so-called floating tree-ring chronology has been established makes it possible to determine an empirical age for this floating tree-ring series based upon the age of the wood used for comparison. For the case of the Swiss Lake Dwellers, the difference between conventional radiocarbon dates and the age values determined in this manner amounts to about 800 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

1968
1968
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 0 publications
1
26
1
Order By: Relevance
“…This results in considerable underestimation in terms of calendar years. Recently, calibration using independent numerical dating methods beyond the limits of annual tree-rings (Ferguson et al 1966) and varved marine sediments, which extend to only c. 14.7 ka (Reimer et al 2004), now allows the calibration of 14 C dates from the LGM and beyond (Fairbanks et al 2005). All 14 C ages in this study are calibrated by the currently most reliable and precise high-resolution marinederived 14 C-dated sedimentological and geochemical record from the Cariaco Basin, tied to the highresolution 230 Th-dated Hulu Cave speleothem record (Hughen et al 2006), using the integrated CalPal-2007 Hulu -calibration dataset (Weninger & Jöris 2008) as part of the CalPal-2007 calibration and palaeoclimate research software package .…”
Section: Flinders Silts Radiocarbon Datesmentioning
confidence: 99%
“…This results in considerable underestimation in terms of calendar years. Recently, calibration using independent numerical dating methods beyond the limits of annual tree-rings (Ferguson et al 1966) and varved marine sediments, which extend to only c. 14.7 ka (Reimer et al 2004), now allows the calibration of 14 C dates from the LGM and beyond (Fairbanks et al 2005). All 14 C ages in this study are calibrated by the currently most reliable and precise high-resolution marinederived 14 C-dated sedimentological and geochemical record from the Cariaco Basin, tied to the highresolution 230 Th-dated Hulu Cave speleothem record (Hughen et al 2006), using the integrated CalPal-2007 Hulu -calibration dataset (Weninger & Jöris 2008) as part of the CalPal-2007 calibration and palaeoclimate research software package .…”
Section: Flinders Silts Radiocarbon Datesmentioning
confidence: 99%
“…However, these potential problems with dendrodating were already well known, and in fact successful dendrochronology identifies these circumstances and corrects for them. In the case of bristlecone pine, Ferguson et al (1966) further argued that examination of 1000 trees did not even reveal any false rings. Additionally, an independent bristlecone pine chronology from a different site in the White Mountains developed by LTRR's V C LaMarche and T P Harlan (1973) back to 3435 BC demonstrated no errors in the original chronology of Ferguson (1970b).…”
Section: Initial Testing Of the Radiocarbon Methodsmentioning
confidence: 99%
“…Thus, dendrochronology is much more than a simple "ring counting" exercise, which could produce significant errors in dating if the false and missing rings are not recognized and accounted for. For example, Ferguson et al (1966) reported that in some instances long-lived bristlecone pines might have 5% or more rings missing along a given radius. At this rate, if simple ring counting was employed, the count would be off by 50 yr or more in a 1000-yr-old tree and 200 yr or more in a 4000-yr-old tree.…”
Section: The Power and Accuracy Of Dendrochronologymentioning
confidence: 99%
“…The discrepancy indicated by radiocarbon analysis of dated sequoia wood and of material from early Egyptian dynasties is substantiated by the results of carbon-14 dating of bristlecone pine wood from comparable time periods. Dual dates, derived from the radiocarbon analysis of tree-ring-dated bristlecone pine wood show that, for material in the period 4000 to 3000 B.C., dates obtained by the conventional carbon-14 method are about 800 years more recent than dates established dendrochronologically (21). There is at present a spirited debate concerning the possible direction and causal nature of this relationship, a point that may be resolved when even earlier wood is found and dated, as we expect it will be.…”
Section: Relation To Radiocarbonmentioning
confidence: 94%